Optimization of six-port device for QPSK demodulation in front-end communication receiver - Noor Suhaira Alia Arshad (School of Computer and Communications Engineering, 2016)
There are two main objectives in the thesis. The aim of this research project is as follows, to design, fabricate and test the six-port device with optimized operational bandwidth, dimensions and S-Parameter performances; to evaluate and analyse the performance of the proposed six-port device as QPSK demodulator in front-end communication receivers.